Genes, Microbes, and T Cells — New Therapeutic Targets in Crohn's Disease - Elson, Charles O (The New England journal of medicine, 2002)
NOD2, a gene conferring susceptibility to Crohn's disease, has been identified on chromosome 16. Homozygosity for a mutation that truncates the gene increases the risk of Crohn's disease by a factor of 20 to 40. No such mutations have been found in patients with ulcerative colitis. NOD2 has a role in apoptosis and in the recognition of microbial endotoxins. Crohn's disease and ulcerative colitis, collectively known as inflammatory bowel disease, affect up to 1 million people in the United States. These related but distinct diseases are complex disorders with immunologic, environmental, and genetic components, each of which is the subject of intense investigation. In 1996 a gene conferring susceptibility to Crohn's disease was identified on chromosome 16 in families with multiple affected members. Now two groups, working independently and using different strategies, have identified the relevant gene at that locus. 1 , 2 The gene is named NOD2, and is similar to the R factor genes of plants that confer resistance . . .